Semi-Transparent, Chiral Organic Photodiodes with Incident Direction-Dependent Selectivity for Circularly Polarized Light - Liu, Lixuan (Advanced materials (Deerfield Beach, Fla.), 2023)
© 2023 The Authors. Advanced Materials published by Wiley-VCH GmbH.